Frontispiece: Investigation of Binding Behavior between Drug Molecule 5‐Fluoracil and M4L4‐Type Tetrahedral Cages: Selectivity, Capture, and Release. Issue 15 (14th March 2017) - Xu, Wei‐Qin; Fan, Yan‐Zhong; Wang, Hai‐Ping; Teng, Jun; Li, Yu‐Hao; Chen, Cheng‐Xia; Fenske, Dieter; Jiang, Ji‐Jun; Su, Cheng‐Yong
Abstract : The cage's size and window are of importance for the host‐guest binding. 5‐Fluoracil can be preferentially captured by MOC‐19 in comparison to the larger MOC‐22 cage. The porous nanoparticle of MOC‐19 exhibits outstanding behaviors to control release of 5‐FU in simulated human body liquid PBS buffer. For more details, see the Communication by J. J. Jiang et al. on page 3542 ff.